Psychosocial impact of perinatal loss among Muslim women - Sutan Rosnah; Miskam Hazlina (BMC, 2012)
Abstract Background Women of reproductive age are vulnerable to psychosocial problems, but these have remained largely unexplored in Muslim women in developing countries. The aim of this study was to explore and describe psychosocial impact and social support following perinatal loss among Muslim women. Methods A qualitative study was conducted in a specialist centre among Muslim mothers who had experienced perinatal loss. Purposive sampling to achieve maximum variation among Muslims in relation to age, parity and previous perinatal death was used. Data was collected by focus group discussion and in-depth unstructured interview until the saturation point met. Sixteen mothers who had recent perinatal loss of wanted pregnancy, had received antenatal follow up from public or private health clinics, and had delivery in our centre participated for the study. All of them had experienced psychological difficulties including feelings of confusion, emptiness and anxiety over facing another pregnancy. Results Two out of sixteen showed anger and one felt guilt. They reported experiencing a lack of communication and privacy in the hospital during the period of grief. Family members and friends play an important role in providing support. The majority agreed that the decision makers were husbands and families instead of themselves. The respondents felt that repetitive reminder of whatever happened was a test from God improved their sense of self-worth. They appreciated this reminder especially when it came from husband, family or friends closed to them. Conclusion Muslim mothers who had experienced perinatal loss showed some level of adverse psychosocial impact which affected their feelings. Husbands and family members were the main decision makers for Muslim women. Health care providers should provide psychosocial support during antenatal, delivery and postnatal care. On-going support involving husband should be available where needed.